2011
DOI: 10.1007/s10120-011-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of S-1 adjuvant chemotherapy for gastric cancer in elderly patients

Abstract: Background The safety and feasibility of administering S-1 adjuvant chemotherapy for gastric cancer has not been fully evaluated in elderly patients. Methods This retrospective study selected patients who underwent curative D2 surgery for gastric cancer, were diagnosed with stage II or III disease, and received adjuvant S-1 at our institution. Patients were categorized into two groups; non-elderly patients (age \70 years: group A) and elderly patients (age C70 years: group B). The toxicity and S-1 continuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Our results showed that patients aged ≥60 years had a survival trend similar to that of patients aged <60 years in different treatment groups, providing further evidence that age does not impact the efficacy of adjuvant therapy in gastric cancer [18], [19]. Female patients who received six cycles failed to show a significant survival benefit compared with those who received four and eight cycles, however, six cycles was associated with a trend toward better survival.…”
Section: Discussionsupporting
confidence: 60%
“…Our results showed that patients aged ≥60 years had a survival trend similar to that of patients aged <60 years in different treatment groups, providing further evidence that age does not impact the efficacy of adjuvant therapy in gastric cancer [18], [19]. Female patients who received six cycles failed to show a significant survival benefit compared with those who received four and eight cycles, however, six cycles was associated with a trend toward better survival.…”
Section: Discussionsupporting
confidence: 60%
“…2 and 3). Aoyama et al (19) reported that in gastric cancer no difference was observed in the RDI of the adjuvant chemotherapy with S-1 in older (≥70 years old) and younger (<70 years old) patients with gastrectomy. However, Tsushima et al (20) demonstrated that median RDI in younger (≤65 years old) patients was likely to be lower compared to older (>65 years old) patients, including patients with unresectable gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A phase III clinical trial of adjuvant chemotherapy and chemotherapy for unresectable gastric cancer was performed, but patients aged 80 and over were excluded . Aoyama et al reported that the incidences of grade III hematological and non‐hematological toxicities of S‐1 adjuvant chemotherapy for the elderly were <5%, and that this regimen was safe and feasible and Tsushima et al reported that S‐1 or S‐1 plus cisplatin for elderly patients presented a high risk of hematological toxicities, but was feasible. However, there were only a few patients aged 80 and older in these studies.…”
Section: Discussionmentioning
confidence: 99%